Clinical Profile, Management and Outcome of Patients Presenting with Acute Pulmonary Embolism at Tertiary Level Cardiac Centre in Nepal - Poudel, Chandra M; Khanal, Rajaram; Gajurel, Ratna M; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Manandhar, Bhawani; Pathak, Surya R (Journal of Institute of Medicine Nepal, 2021)
Introduction Pulmonary embolism (PE) is a common, under diagnosed and potentially lethal clinical condition. The aim of our study was to find out the clinical profile, management and outcome of patients with acute PE. Methods It was a retrospective study. The participants included patients admitted and diagnosed to have acute PE from January 2014 to December 2019. Patients with high clinical probability and positive D-dimer in low and intermediate clinical probability were diagnosed as acute PE clinically. Data were obtained from the records section of the hospital. Results The most common risk factor was found to be smoking. Only two patients were found to have protein C and protein S deficiency (4.4%) and one patient had hyperhomocysteinemia (2.2%). The most common symptom was found to be shortness of breath (97.8%). The most common sign was sinus tachycardia. Right ventricular dysfunction was found in 35.5% of the patients on echocardiogram. Computerized tomography pulmonary angiogram (CTPA) was done in 60% of the patients. The most common CT finding was presence of thrombus in main pulmonary artery in 13.3% of patients. Troponin I was positive in 26.7% of patients and D-dimer was positive in 66.7%. Only 42.2% had evidence of deep vein thrombosis. Only 13.3% were thrombolysed. All the patients received low molecular weight heparin or unfractionated heparin followed by warfarin or dabigatran. The in-hospital mortality rate was 15.6% where the rest of the patients were discharged. Conclusion The most common symptom and sign was found to be shortness of breath and sinus tachycardia. Single investigation was not conclusive so multiple investigations were done to reach the diagnosis. Though all the patients received anticoagulation, only few of them were thrombolysed. The in-hospital mortality was found to be 15.6%.